Age at first marriage and women’s psychosocial wellbeing in the Amhara region, Ethiopia - Mikyas Abera; Ansha Nega Ahmed; Yifokire Tefera Zele (BMC Women's Health)
Abstract Background Early marriage is a public health problem with damaging ramifications for all affected, especially young women's well-being. It affects millions globally—with the majority living in South Asia and Sub-Saharan Africa. The Amhara region of Ethiopia remains one of the hotspots of child marriage. Methods This study employed a cross-sectional study design and used a mixed-method approach to collect data on age at first marriage, community values on marriage, and women’s social capital and self-esteem. It drew on social capital and self-esteem theorists to construct a survey questionnaire, focus group discussion, and interview guides. It employed descriptive and inferential statistics and thematic analyses to explore empirical data. Results This study found no and weak statistically significant differences in global estimates of women’s social capital and self-esteem due to their age at first marriage, respectively. However, women married ≥ 25 years measured better on social capital and self-esteem indicators, especially compared to those married between 15–17 years. Qualitative findings provided insights into potential confounding factors and grounded explanations of survey findings vis-à-vis existing literature on the psychosocial effects of early marriage on women. Conclusion Global estimates of women’s psychosocial well-being were not significantly associated with age at first marriage. FGDs and interviews indicated that the Amhara value and treat marriage primarily as a means for intergenerational continuity and family alliances. Marrying a woman early is desirable, ensures longer reproductive years, protects the purity of the paternal line, and grants girl-children improved social status and desirability. The authors recommend researchers design standard self-assessment survey tools, considering cultural and systemic contexts in collectivistic communities.